2019
DOI: 10.3390/ijms20071624
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations in LysM Domains of LysM-RLK PsK1 May Result in a Different Effect on Pea–Rhizobial Symbiosis Development

Abstract: Lysin-motif receptor-like kinase PsK1 is involved in symbiosis initiation and the maintenance of infection thread (IT) growth and bacterial release in pea. We verified PsK1 specificity in relation to the Nod factor structure using k1 and rhizobial mutants. Inoculation with nodO and nodE nodO mutants significantly reduced root hair deformations, curling, and the number of ITs in k1-1 and k1-2 mutants. These results indicated that PsK1 function may depend on Nod factor structures. PsK1 with replacement in kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…It should be noted that PsK1 is specifically involved in legume– Rhizobium symbiosis, but is not required for the interaction with arbuscular mycorrhizal fungi. However, the increased sensitivity of Psk1-1 and Psk1-2 to Fusarium culmorum may indicate the possible involvement of PsK1 in the immune response [ 94 ].…”
Section: Identification Of Symbiotic Regulatory Genes In Peamentioning
confidence: 99%
“…It should be noted that PsK1 is specifically involved in legume– Rhizobium symbiosis, but is not required for the interaction with arbuscular mycorrhizal fungi. However, the increased sensitivity of Psk1-1 and Psk1-2 to Fusarium culmorum may indicate the possible involvement of PsK1 in the immune response [ 94 ].…”
Section: Identification Of Symbiotic Regulatory Genes In Peamentioning
confidence: 99%
“…Since NF perception requires a heterodimeric receptor with LYR and LYK subunits, we considered the LykX gene as encoding the LYR subunit, and the conventional Sym10 gene as encoding the LYK subunit. The Sym10 gene was demonstrated to be required for the legume-rhizobia symbiosis development, and the possibility of Sym10-Sym37 and Sym10-K1 complexes formation was also shown (Kirienko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Only several attempts to show such binding have been successful to date (Broghammer et al, 2012;Kirienko et al, 2018). The difficulty of this detection may be caused by the fact that legume NF receptors work in heterodimers (Xiao et al, 2014;Igolkina et al, 2018;Kirienko et al, 2019), whereas modern technologies are aimed to test the "one receptor-one ligand" model. Additionally, NF isolation and purification are very time-and resourceconsuming procedures, while the chemical synthesis of NF is extremely difficult due to the high complexity of its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we described the role of LysM-RLK K1 in controlling the symbiosis development in pea P. sativum L. Analysis of mutants impaired in this gene, as well as a number of other evidences, suggested that K1 can control both early symbiotic reactions (deformations and curling of root hairs) and later ones associated with the development of IT in the root cortex of plants and the release of bacteria from IT [12,19]. Studying the effect of expression of this gene in the epidermis under the pLeEXT1 promoter on events occurring in the root cortex may be a convenient tool for identifying the relationship between the developmental programs in different types of tissues in pea during symbiosis.…”
Section: Introductionmentioning
confidence: 99%